2020
DOI: 10.7251/ghte1915009p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cr(VI) adsorption from aqueous medium onto bentonite

Abstract: Because of its abundance and toxicity, heavy metals have become a seriousenvironmental problem. The presence of heavy metals, such as Cr(VI), in thewatercourses leads to numerous health problems in humans and animals. Cr(VI) ishighly toxic, even in low concentrations. Because of its carcinogenic, mutagenic andteratogenic effects on human beings, Cr(VI) is considered one of the most criticalpollutants. Due to this, it is necessary to remove Cr(VI) from wastewater prior to itsdischarge into the recipient.This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The analysis of the diffraction maxima confirmed the presence of montmorionite (M), while the other crystalline phases were quartz (Q) and cristobalite (C) [26]. Similar values of the diffraction maximums on the bentonite sample were also obtained by Petrović R. et al and Ranđelović M. et al [27,28].…”
Section: Fig 1 Point Of Zero Charge Of Bentonitesupporting
confidence: 69%
See 2 more Smart Citations
“…The analysis of the diffraction maxima confirmed the presence of montmorionite (M), while the other crystalline phases were quartz (Q) and cristobalite (C) [26]. Similar values of the diffraction maximums on the bentonite sample were also obtained by Petrović R. et al and Ranđelović M. et al [27,28].…”
Section: Fig 1 Point Of Zero Charge Of Bentonitesupporting
confidence: 69%
“…However, very little research can be found on applications for removal from galvanic wastewater. Large specific surface area, high ion exchange capacity, chemical and mechanical stability are properties of clay, which have an affinity for the adsorption of cationic, anionic and neutral metal forms [14]. Thanks to its good properties, low price and wide distribution, bentonite has become a material that is increasingly used in environmental protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation